Meningkatkan Kemampuan Pemecahan Masalah Pada Pembelajaran Matematika Menggunakan Model Berkat Untuk Siswa Kelas IV SDN Manduin - Muhammad Wahyudha; Maimunah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research focuses on the main issue of students' low problem-solving skills and their learning outcomes in mathematics. Inadequate mathematics teaching methods in developing problem-solving skills have been identified as the primary cause. To address this issue, the BERKAT model was implemented. The aim of this research is to describe the activities conducted by both teachers and students and to evaluate the improvement in problem-solving skills and academic achievement. This study employs a qualitative method using the Classroom Action Research (CAR) approach, conducted over four meeting sessions. The research involved 15 fourth-grade students from SDN Manduin during the second semester of the 2023/2024 academic year. The findings indicate that the interaction between the teacher and students was highly effective. Additionally, there was significant progress in problem-solving skills and academic achievement, reaching 100% by the fourth session. Based on these findings, it can be concluded that the implementation of the BERKAT model is highly effective in enhancing the learning process, as evidenced by the significant improvement in students' problem-solving skills and academic outcomes.